2021
DOI: 10.1088/1681-7575/ac1e35
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of predictable quantum efficient detector in terms of optical non-linearity in the visible to near-infrared range

Abstract: Characteristics of predictable quantum efficient detector (PQED) by in terms of optical nonlinearity in the visible to near-infrared range were investigated under zero-bias and reverse-bias voltage conditions. In the zero-bias condition, linear behavior was observed in the wavelength from 405 nm to 1060 nm in the photocurrent range of 1 nA to 10 µA, and saturation occurred for photocurrents over 10 µA for all wavelengths. In the reverse-bias voltage of 10 V, the linear behavior was observed in the photocurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…However, as shown figures 12(c) and (d), it occasionally occurs the increase of supralinearity value for Si PD C because the starting photocurrent of saturation for Si PD increases by applying the reverse-bias voltage to it. We have confirmed that this phenomenon has occurred in other Si PD as well [28]. The Si PD in which this phenomenon occurs would be difficult to use for accurate optical measurements even after nonlinearity correction.…”
Section: Nonlinearity Characteristics Of Silicon Pds Under Reverse-bi...supporting
confidence: 77%
See 1 more Smart Citation
“…However, as shown figures 12(c) and (d), it occasionally occurs the increase of supralinearity value for Si PD C because the starting photocurrent of saturation for Si PD increases by applying the reverse-bias voltage to it. We have confirmed that this phenomenon has occurred in other Si PD as well [28]. The Si PD in which this phenomenon occurs would be difficult to use for accurate optical measurements even after nonlinearity correction.…”
Section: Nonlinearity Characteristics Of Silicon Pds Under Reverse-bi...supporting
confidence: 77%
“…In all the previous studies, linearity of the Si PD with respect to the incident optical flux at widely incident wavelengths was fundamental for determining the highly accurate absolute optical flux at a range greater than six orders of magnitude. Various studies have been conducted on linearity and nonlinearity measurements using various type of Si PDs [26][27][28]. In general, an ideal Si PD is linear when the photoelectric response is proportional to the incident optical flux.…”
Section: Introductionmentioning
confidence: 99%
“…The PQED photodiodes with SiO 2 coating were originally manufactured from low-doping p type silicon [75]. It is also possible to make PQED photodiodes from low-doped n type silicon, but then Al 2 O 3 has been used as the coating material to produce the induced junction [90,91]. The charge-carrier recombination losses of n type photodiodes appear to be somewhat larger than those of p type photodiodes.…”
Section: Measurement Of Optical Powermentioning
confidence: 99%